A voz das crianças e suas professoras: concepções de criança, infâncias e práticas pedagógicas nos contextos da educação infantil - Cogo, Janaína Raquel (2024)
This thesis is linked to the Research Line: Educational public policies, educational practices and their interfaces, of the Postgraduate Program in Education - Doctorate in Education of the Federal University of Santa Maria and has as its theme the concepts of childhood, children and practice pedagogical approach for children and teachers in the context of early childhood education. The general objective of the research is to investigate the conceptions of childhood produced by early childhood education teachers at a public school in the city of Santa Rosa/RS through their narratives and the conceptions that children express in their interactions concerning pedagogical practices and approaches in early childhood education from a decolonizing perspective of childhood and practices for childhood. To achieve the objectives, two arguments are considered that summarize the defended thesis. The first argument is that Perceptions of childhood are implicated in pedagogical practices and educational relationships that are established between adults and children in early childhood education. The second argument is that from a decolonizing perspective of childhood, we can build pedagogical practices that value childhood's potential, enriching educational relationships between adults and children in early childhood education. The research has a qualitative approach and was carried out with two audiences: teachers and children in early childhood education. The research subjects were four teachers and twenty-two children aged 3 to 4 years old from a nursery class at a municipal early childhood education school in the city of Santa Rosa/RS. The research with children was participant observation from February to October 2023. Data analysis used reflective sociology and the sociology of childhood. In the research with children, it was noticed how children in their games not only reproduce scenes from everyday adult life but also construct, reconstruct, and re-elaborate concepts, building children's cultures and contributing to adult cultures. The research with early childhood education teachers comprised focus group meetings in November and December 2023. The data analysis was carried out using the discursive textual analysis approach. From field research with teachers, listening to their voices and manifestations, it was understood that they have perceptions of differences between contemporary childhood and their childhood memories, which involve the difference in the way they play and interactions related to aspects of the contemporary context of fear, violence, and acceleration of the time in which we live. The study is anchored in history in authors such as Kuhlmann Jr. (2001, 2002), Del Priore (2020), Freitas (2016), in philosophy in authors such as Kohan (2011), Benjamin (2009), Gallo (2019), in sociology, to think about pedagogy for childhood with a decolonizing perspective, authors such as Faria (2011, 2021), Malaguzzi (2016), Abramovicz (2011, 2015, 2019).